Effects of a targeted blood management programme on allogeneic blood transfusion in abdominal aortic aneurysm surgery. Issue 4 (15th December 2017) - Stoneham, M. D.; Von Kier, S.; Harvey, L.; Murphy, M.
SUMMARY: Objectives: To investigate the impact of a dedicated cell salvage practitioner team on blood loss and allogeneic transfusion in abdominal aortic aneurysm (AAA) surgery. Background: Cell salvage reduces allogeneic transfusion in AAA surgery, but is commonly performed by the anaesthetic nurse. At our hospital, a dedicated patient blood management practitioner is present for all elective open AAA repairs. Methods/Materials: Data were collected on 171 AAA patients operated on at the John Radcliffe Hospital, Oxford over a 3‐year period, looking at the Patient Blood Management processes, including: blood loss, cell salvage, near‐patient testing (thrombelastography) and transfusion rates of allogeneic blood products. Results: Blood loss ranged from 3–108% of estimated blood volume (EBV) (median 25% = 1500 mL). In seven patients who lost 70–110% of their EBV, none reached the thrombelastography intervention threshold for R time (11 min) or MA (48 mm) despite such massive blood loss. Overall, only 7/171 (4%) patients received intra‐operative allogeneic blood, all of whom had a mean baseline haemoglobin concentration < 106 g L −1 (median 98, range 95–105 g L −1 ). In terms of other blood products, only 4/171 (2·3%) received one unit of platelets each intra‐operatively. None received FFP or cryoprecipitate. Conclusions: Such low levels of allogeneic transfusion have not been reported previously. We hypothesise that this is due to the additional blood management contributions of the specialised cell salvage practitioners and collaboration with the rest of the vascular surgical team. These results support the development of pre‐operative anaemia clinics. Overall the service runs at a profit to the trust.